Zita the spacegirl : Far from home - Hatke, Ben. (New York : First Second, 2010)
Zita rushes to the rescue after her best friend is abducted by an alien doomsday cult, and, before long, finds herself hailed as an intergalactic hero.
School Library Journal, January 2011.
Booklist, December 2010.
Bulletin (Center for Children's books), January 2011.
Teacher Librarian, February 2011.
Kirkus Review, December 2010.
Library Media Connection, March 2011.
Keywords: Human-alien encounters -- Juvenile fiction; Extraterrestrial beings -- Juvenile fiction; Human-alien encounters -- Comic books, strips, etc. -- Fiction; Aliens (Fictional characters) -- Comic books, strips, etc. -- Fiction; Quests (Expeditions) -- Comic books, strips, etc. -- Fiction; Science fiction comic books, strips, etc; Quests (Expeditions) -- Juvenile fiction; Graphic novels; Graphic novels